Clinical Spectrum and Burden of Influenza-Associated Neurological Complications in Hospitalised Paediatric Patients - Yu, Michael Kwan Leung; Leung, Cherry Pui Pik; Wong, Wilfred Hing Sang; Ho, Alvin Chi Chung; Chiu, Annie Ting Gee; Zhi, Helen Hui; Chan, Godfrey Chi Fung; Chan, Sophelia Hoi Shan (Frontiers in Pediatrics, 2022)
Background: Influenza is one of the most common causes of acute respiratory tract infections around the world. Influenza viruses can cause seasonal epidemics. There remains limited information on the impact of both seasonal influenza A and influenza B related hospitalisations from neurological complications in paediatric populations in Asia. Objectives: To examine both the clinical spectrum and healthcare burden of influenza-associated neurological complications (IANCs) within the paediatric population of Hong Kong. Methods: We conducted a population-based retrospective study to identify all paediatric patients (<18 years) admitted to a public hospital in Hong Kong with a confirmed influenza A or B infection between 2014 and 2018 using the Clinical Data Analysis and Reporting System of the Hospital Authority. The clinical spectrum of the paediatric patients with IANCs was studied. The clinical burden of paediatric influenza patients with IANCs were compared to paediatric influenza patients without neurological complications. Results: A total of 28,016 children admitted to the paediatric wards diagnosed to have influenza A or B infection were identified, accounting for 5.7% (28,016/489,955) of total paediatric admissions. 67.3% had influenza A and 32.7% had influenza B, and 8.9% had IANCs. The mean annual incidence of IANCs in children was 57 per 100,000 population. The spectrum of IANCs in our paediatric patients included febrile seizures (80.6%), myositis (11.4%), seizures with fever (5.4%), influenza-associated encephalitis/encephalopathy (IAE) (2.6%) and rarely Guillain–Barré syndrome (0.04%). Most paediatric patients with IANCs (85.5%) presented at a young age of <6 years. Paediatric patients with IANCs had significant longer hospital stays (p<0.001), higher percentages of mechanical ventilation use (p<0.05) and PICU admissions (p<0.001), and higher mortality rates (p<0.001) compared to those without neurological complications. Amongst those with IANCs, IAE was the sole cause of all seven reported mortalities. Conclusions: Seasonal influenza A & B is a common cause of hospitalisation for paediatric patients in Hong Kong. We found neurological complications from influenza A and B caused a significantly higher clinical burden compared to those without neurological complications. Children in younger age groups (<6 years old) are at highest risk and thus increasing vaccination coverage to this age group is recommended.